Proceedings of the Proceedings of the 2nd International Conference on Quran and Hadith Studies Information Technology and Media 2020
DOI: 10.4108/eai.2-10-2018.2295460
|View full text |Cite
|
Sign up to set email alerts
|

Developing Social Studies Teaching Materials Based on Multimedia EPUB for The Effectiveness on Learning Outcomes

Abstract: The aims of this study 1) to develop of Social Studies teaching materials based on multimedia EPUB 2) To determine the effectiveness on learning outcomes of the development of social studies teaching materials based on multimedia EPUB. This study uses a development method based on the Dick and Carrey model. 1) The results of the development are informed from the validation of material experts who get 85% in the effective category. The results of the validation of linguists, media and design experts receive 89%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…It showed that the average score of students after using EPUB had increased. Another evidence by (Islamy et al, 2020) with research results of 72%, a posttest increase was affected by the successful use of EPUB instructional materials.…”
Section: Description Of Final Evaluation (Evaluation)mentioning
confidence: 78%
“…It showed that the average score of students after using EPUB had increased. Another evidence by (Islamy et al, 2020) with research results of 72%, a posttest increase was affected by the successful use of EPUB instructional materials.…”
Section: Description Of Final Evaluation (Evaluation)mentioning
confidence: 78%